The Views of Bayan Village Religious Figures About Weak Women in a Bayan Traditional Wedding, North Lombok District - Khairi, Muazzam; Hamim, Khairul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research examines the views of village religious leaders Bayan Regarding Awik-awik Kirangan in Bayan Traditional Weddings North Lombok Regency, to find out what the figures think Bayan Village religion regarding awik-awik kirangan in traditional marriages parrot. The research method used in this research is Descriptive Qualitative Research. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation and drawing conclusions. Meanwhile, the research location in this study was Bayan Village, Bayan District, North Lombok Regency. The results of the research show that, this kirangan awik-awik still carried out until now since the wedding until now. According to the views of religious figures, awik-awik This thought will be a secret/safety, no problem religion and does not conflict because it has become a mutual agreement. The reason is because it has become a mutual agreement on during the gundem (customary deliberation) event and has become a standard decision Bayan indigenous people who cannot be changed.